Pengaruh Metode Bermain Peran Berbasis Joyful Learning terhadap Peningkatan Keterampilan Berbicara Siswa Sekolah Dasar Kelas VI: The Effect of Joyful Learning-Based Role-Play Method on Improving the Speaking Skills of Grade VI Elementary School Students - Tutik Sri Muntamah; Hendratno Hendratno; Nurul Istiq’faroh (ITScience (Information Technology and Science), 2026)
Speaking skills are among the important competencies in Indonesian language learning in elementary schools because they relate to students' abilities to express ideas, communicate effectively, and interact in social environments. However, in practice, students' speaking skills remain relatively low because the learning process remains teacher-centered and does not provide opportunities for active speaking practice. This study aims to analyze the effect of the Joyful Learning-based role-playing method on improving the speaking skills of sixth-grade students at SDN Gugus VI Sepaku. This study uses a quantitative, experimental approach with a pretest–posttest control-group design. The research subjects were 54 students, comprising 27 in the experimental group and 27 in the control group. Data collection techniques included speaking skills tests and observations of student activities. Data analysis used descriptive statistics, normality and homogeneity tests, and Independent-Samples t-tests. The results showed that the average score for students' speaking skills in the experimental group increased from 59.44 in the pretest to 83.56 in the posttest, whereas in the control group it increased from 58.59 to 69.26. The results of the hypothesis test showed a significance value of 0.000 < 0.05, indicating a significant difference between the two groups. The N-Gain analysis also showed greater improvement in the experimental group than in the control group. Thus, the Joyful Learning-based role-playing method has proven effective in improving elementary school students' speaking skills.